Role of Capital Formation and Saving in Promoting Economic Growth in Nepal: An ARDL Bound Testing Approach - , Arjun Kumar Dahal; , Ananta Jiban Luitel (Archives of Current Research International, 2021)
This study examines the relation and impact of gross capital formation and gross national saving on Nepal's Gross Domestic Product (GDP). It is based on the secondary data taken from various economics survey of Nepal and other published sources covering 33 data points from the fiscal year 1987/88 to 2019/20. Descriptive and empirical research designs examine the relation between GDP, gross capital formation, and gross national saving. The EViews 10 data processing software is used. Some econometrics tools like mean, dispersion, ARDL bound testing, error correction model, heteroskedasticity, serial correlation test, normality test, CUSUM test, and CUSUM square test are used. There is a long-run positive relationship between GDP and gross capital formation and gross national saving. The gross capital formation and gross national saving are individually and jointly significant to explain GDP in the long run, but there is a negative impact on regressors' GDP. Capital formation and saving positively impact GDP. Still, the effectiveness is not found satisfactory because a one percent increase in capital formation only increases GDP by 0.267 per cent. So, the saving amount must be utilized in the productive sector. The author of the research is not affected by the other researchers' findings, tools, and methods.